Revision of Gallerucida singularis species group (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng; Bezdĕk, Jan (Zootaxa, 2013)
The Gallerucida singularis species group is established. Gallerucida gebieni Weise, status restored and G. haroldi Weise, status restored are resurrected from synonymy with G. singularis Harold. Lectotypes are designated for G. haroldi and G. tonkinensis Laboissière. The species are differentiated mainly based on the structure of the endophallic sclerites.